MAGIC AND SUBVERSION: WEAVING REALITY’S FABRIC - Negrini Silva, Frederico (Abusões, 2025)
Magic is a fundamental element present in Fantasy works and an under analyzed aspect of such genre and mode. We will attempt to provide an open-ended definition of Magic as a modal aspect of Fantasy, whose function lies in the very process that subverts and transforms reality intratextually and/or intertextually. Concomitantly we will argue that such definition is better fit within a processual and organic metaphysical framework, especially due to Magic’s power to erase ontologically absolute layers of the world. Such subversive capacity, as Magic reimagines reality and weaves processes in new actualized concrescences, is a constant reminder of the inexorable limits of any given system and its ultimate lack of concreteness — such latter terms are often understood as a reifiying attempt forced by the collectively established mental constructs and the dominant cultural order. Due to its raw and core unbound potentiality and by understanding Magic modally, we can extend its presence to most if not all non-mimetic fictionalized productions through its defining capacity of enabling and performing subversion.